Aid and institution-building in fragile states: The case of Somali-inhabited eastern Horn of Africa - Ken Menkhaus (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Institution-building in Somalia has met with high levels of failure for two decades. But successes have occurred in other Somali-inhabited regions of the eastern Horn, and have been especially present at the local and municipal level. The most effective aid to institution-building in Somalia has been carefully calibrated support to hybrid local governance arrangements that enjoy a strong degree of local ownership and which deliver practical, urgently needed services.
Keywords: O1; O2; O19; 330; Somalia; failed state; institution-building; local governance; municipalities; hybrid state